CHANGE IN REACTIVE OXYGEN SPECIES GENERATION WHEN A BODY IS AFFECTED BY USED ENGINE OIL IN WHITE RATS’ TESTIS - Соловйова, Н.В. (World of Medicine and Biology, 2015)
Generation of reactive oxygen species (1О2, .О , Н2О2, ОН, NО, Rо2 etc.) is an integral part of functioning of living cells in human and animal bodies. Where inflammation develops, a contribution to reactive oxygen species generation might lead to a “respiratory explosion” of white blood cells. The processes of reactive oxygen species transformation are intensified by multiple valence metal ions. Such general scheme of reactive oxygen species generation is consistent with the availability of the said structures and enzymes in testis cells, but requires further experimental research. We have studied the change in generation of reactive oxygen species in white rats’ testis at the time their bodies were affected by used engine oil. We found that over time, in case of long-term effect of used engine oil on the body of white rats, the amount of superoxide anion radical generated in testis tissues through mitochondrial electron transport chain is growing. The increased generation of superoxide in testis through microsomal electron transport chain is time-constrained and is observed on the 60th day after the commencement of giving used engine oil to rats by injection. Superoxide anion radical generation by leukocyte NADPH oxidase in white rats’ testis tissues on condition of used engine oil injection demonstrates certain phasicity: it increases considerably on 14th-30th day and reduces on the 90th day.
Keywords: superoxide anion radical; antioxidant enzymes; testicles; used motor oil